egulating e-commerce in Algeria: The National Card for Electronic Suppliers as a Model - Rahali, Siefeddine; lakehal, Nora (Journal of Excellence for Economics and Management Research, 2025)
E-commerce, like other commercial practices, requires certain conditions to be met in order to be practiced. This is what the Algerian legislator has approved in Law No. 18-05 on e-commerce - which is considered the first independent law regulating e-commerce transactions in Algeria - therefore our study aimed to shed light on the fact that the national card for electronic suppliers is considered a basic regulator for practicing this type of trade, due to the importance of this card in controlling the virtual market on the one hand, and in protecting the electronic consumer on the other hand. The problem of our research focused in particular on the legal status of persons who engage in e-commerce activity through social networking sites, for example, without being members of this card, and the extent to which they are subject to the provisions of the aforementioned law? In order to answer this problem, we relied on the analytical and descriptive approaches, to finally reach the most important result, which is that the National Center for the Commercial Registry is responsible for creating this card through its electronic portal. We also suggested to the concerned center the necessity of facilitating the joining of this card by merchants and craftsmen.